PENGARUH PERANAN GURU DAN EFIKASI DIRI SISWA TERHADAP MINAT BELAJAR KOMPETENSI KEAHLIAN PEMASARAN SISWA KELAS X PEMASARAN DI SMK NEGERI 1 KOTA PROBOLINGGO - Indah Fajarwati (Jurnal Penelitian dan Pendidikan IPS, 2016)
This study aims to know the influence of teachers’ role and students’ self-efficacy to learning interest of marketing of tenth graders of marketing department at SMK Negeri 1 Probolinggo. The respondents of this study were seventy six (76) tenth graders of marketing department. As the result, teachers’ role and students’ self-efficacy influence significantly to marketing learning interest.